Algorithms and Computation 20th International Symposium, ISAAC 2009, Honolulu, Hawaii, USA, December 16-18, 2009. Proceedings - Dong, Ying Fei; Du, Ding-Zhu; Ibarra, Oscar H. (Theoretical Computer Science and General Issues,, 2009)
This book constitutes the refereed proceedings of the 20th International Symposium on Algorithms and Computation, ISAAC 2009, held in Honolulu, Hawaii, USA in December 2009. The 120 revised full papers presented were carefully reviewed and selected from 279 submissions for inclusion in the book. This volume contains topics such as algorithms and data structures, approximation algorithms, combinatorial optimization, computational biology, computational complexity, computational geometry, cryptography, experimental algorithm methodologies, graph drawing and graph algorithms, internet algorithms, online algorithms, parallel and distributed algorithms, quantum computing and randomized algorithms.